ADAPTASI MODEL KEMATANGAN NHS INFRASTRUCTURE (NIMMTM) UNTUK EVALUASI INFRASTRUKTUR TI PADA RUMAH SAKIT DI YOGYAKARTA - Danny Sebastian; Benyamin L Sinaga; Sapty Rahayu (Universitas Kristen Duta Wacana, 2016)
IT infrastructure is an important for a company to achieve competitive advantages. All bussiness industry needs a good IT infrastructure to support their business, it also experienced by healthcare industry. However in Indonesia, there is no standarisation for IT infrastructure in hospital. The purpose of this research is to adapt NHS infrastructure maturity model (NIMMTM) based on Indonesian hospital environment, in this case RS XYZ. This research consist of 3 steps, preliminary study (1), maturity model adaptation (2), and maturity model validation (3). The adapted maturity model consist of 11 categories and 60 key capabilities. Each key capabilities has 5 perspectives, process perspective, organisation & people perspective, technology perspective, IT security & information governance perspective, and strategy alignment & business value perspective. Each perspective has at least 1 KPI and total KPI of this adapted maturity model is 432 KPIs. The adapted maturity model can be used for IT infrastructure maturity evaluation and a guidelines for enhance IT infrastructure.